Fluid mechanics fundamentals and applications, - Cengel, Yunus A.
"Fluid Mechanics: Fundamentals and Applications communicates directly with tomorrow's engineers in a simple yet precise manner. The text covers the basic principles and equations of fluid mechanics in the context of numerous and diverse real-world engineering examples. The text helps students develop an intuitive understanding of fluid mechanics by emphasizing the physics, and by supplying attractive figures, numerous photographs and visual aids to reinforce the physics."--Jacket.